Predicative adjectives in Thai: diachronic changes in the past century - Jaratjarungkiat, Sureenate (2022)
The present study has two main aims. The first is to categorize predicative adjectives in Thai in order to bring to light a rarely-mentioned group of adjectives that differ from prototypical adjectives. The second is to explain the diachronic changes that took place with regard to Thai adjectives by contrasting their behavior in two different eras–the Rama V era (from 1868 to 1910) and Modern Thai. The results of the present study show that predicative adjectives in Thai can be categorized int o two different groups: prototypicaladjectives and peripheraladjectives. Prototypical adjectives constitute the majority of adjectives used since the past and are syntactically similar to verbs (e.g. they may co-occur with the negation marker /mây/, auxiliary verbs, but not with the copula /pen/), even to the extent of being regarded as a subclass of verbs. Peripheral adjectives, on the other hand, bear resemblance to both nouns and verbs from a syntactic standpoint (e.g. they may co-occur with the negation marker, auxiliary verbs and even the copula /pen/). A comparison between the adjectives of the two eras reveals a total of 18 adjectives (e.g. /sabaay/ ‘comfortable,’ /thùuk/ ‘correct’) that may co-occur with the copula /pen/ in the Rama V era but not in Modern Thai. The reason behind this change is that these 18 adjectives once shared a noun-like property in which they performed the function of abstract nouns, but have since lost this property which accounts for why they may no longer co-occur with the copula /pen/. This change is accounted for by two parameters of grammaticalization: desemanticization and decategorialization.